Insufficient Antigen Presentation Due to Viral Immune Evasion Explains Lethal Cytomegalovirus Organ Disease After Allogeneic Hematopoietic Cell Transplantation - Holtappels, Rafaela; Schader, Sina I.; Oettel, Oliver; Podlech, Jürgen; Seckert, Christof K.; Reddehase, Matthias J.; Lemmermann, Niels A. W. (Frontiers in Cellular and Infection Microbiology, 2020)
Reactivation of latent cytomegalovirus (CMV) poses a clinical problem in transiently immunocompromised recipients of hematopoietic cell (HC) transplantation (HCT) by viral histopathology that results in multiple organ manifestations. Compared to autologous HCT and to syngeneic HCT performed with identical twins as HC donor and recipient, lethal outcome of CMV infection is more frequent in allogeneic HCT with MHC/HLA or minor histocompatibility loci mismatch between donor and recipient. It is an open question if a graft-vs.-host (GvH) reaction exacerbates CMV disease, or if CMV exacerbates GvH disease (GvHD), or if interference is mutual. Here we have used a mouse model of experimental HCT and murine CMV (mCMV) infection with an MHC class-I mismatch by gene deletion, so that either HCT donor or recipient lack a single MHC class-I molecule, specifically H-2 Ld. This particular immunogenetic disparity has the additional advantage that it allows to experimentally separate GvH reaction of donor-derived T cells against recipient's tissues from host-vs.-graft (HvG) reaction of residual recipient-derived T cells against the transplanted HC and their progeny. While in HvG-HCT with Ld-plus donors and Ld-minus recipients almost all infected recipients were found to control the infection and survived, almost all infected recipients died of uncontrolled virus replication and consequent multiple-organ viral histopathology in case of GvH-HCT with Ld-minus donors and Ld-plus recipients. Unexpectedly, although anti-Ld-reactive CD8+ T cells were detected, mortality was not found to be associated with GvHD histopathology. By comparing HvG-HCT and GvH-HCT, investigation into the mechanism revealed an inefficient reconstitution of antiviral high-avidity CD8+ T cells, associated with lack of formation of protective nodular inflammatory foci (NIF) in host tissue, selectively in GvH-HCT. Most notably, mice infected with an immune evasion gene deletion mutant of mCMV survived under otherwise identical GvH-HCT conditions. Survival was associated with enhanced antigen presentation and formation of protective NIF by antiviral CD8+ T cells that control the infection and prevent viral histopathology. This is an impressive example of lethal viral disease in HCT recipients based on a failure of the immune control of CMV infection due to viral immune evasion in concert with an MHC class-I mismatch.